THE USE OF AUDIOVISUAL MEDIA TO IMPROVE ENGLISH LISTENING ABILITY ON X CLASS STUDENTS OF SMK NEGERI 4 LAHAT HOSPITALIZATION DEPARTMENT IN ACADEMIC YEAR OF 2018/2019 - Afrida (Transpublika Publisher, 2022)
This research was conducted in SMK Negeri 4 Lahat whose students' ability to listen to English is quite low. The purpose of writing this classroom action research (CAR) is to find out whether Audio-Visual media can increase student activity and achievement. The data collection methods are observation and learning achievement tests. The data analysis method is descriptive both for qualitative data and for quantitative data. The results obtained from this study are Audio-Visual can increase student learning activities and achievement. This is evident from the results obtained in Cycle I is 6,5 for learning achievement. From Cycle I to Cycle II it rose to 8,3 for learning achievement. The conclusion obtained from this research is that Audio-Visual media can improve learning achievement.